The Application of Curve Fitting on the Voltammograms of Various Isoforms of Metallothioneins-Metal Complexes - Merlos Rodrigo, Miguel Angel; Molina-López, Jorge; Jimenez Jimenez, Ana Maria; Planells Del Pozo, Elena; Adam, Pavlina; Eckschlager, Tomas; Zitka, Ondrej; Richtera, Lukas; Adam, Vojtech (International journal of molecular sciences, 2017)
The translation of metallothioneins (MTs) is one of the defense strategies by which organisms protect themselves from metal-induced toxicity. MTs belong to a family of proteins comprising MT-1, MT-2, MT-3, and MT-4 classes, with multiple isoforms within each class. The main aim of this study was to determine the behavior of MT in dependence on various externally modelled environments, using electrochemistry. In our study, the mass distribution of MTs was characterized using MALDI-TOF. After that, adsorptive transfer stripping technique with differential pulse voltammetry was selected for optimization of electrochemical detection of MTs with regard to accumulation time and pH effects. Our results show that utilization of 0.5 M NaCl, pH 6.4, as the supporting electrolyte provides a highly complicated fingerprint, showing a number of non-resolved voltammograms. Hence, we further resolved the voltammograms exhibiting the broad and overlapping signals using curve fitting. The separated signals were assigned to the electrochemical responses of several MT complexes with zinc(II), cadmium(II), and copper(II), respectively. Our results show that electrochemistry could serve as a great tool for metalloproteomic applications to determine the ratio of metal ion bonds within the target protein structure, however, it provides highly complicated signals, which require further resolution using a proper statistical method, such as curve fitting.
Keywords: spektrometrie hmotnostní - ionizace laserem za účasti matrice; elektrolyty; kovy; electrochemistry; komplexní sloučeniny; Electrolytes; mass spectrometry MALDI-TOF; Protein Isoforms; Sodium Chloride; Protein Binding; vazba proteinů; protein - isoformy; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; metallomics; Metallothionein; Electrochemistry; signal resolving; Coordination Complexes; elektrochemie; metalothionein; chlorid sodný; Metals; metallothionein